Enforcing Nonjusticiable Rights In Indonesia - Andy Omara (The Constitutional Court of the Republic of Indonesia, 2020)
A debate over which branch of government is the most appropriate institution to deal with economic and social rights is far from ended. Is it the legislature which is democratically elected or the unelected Court that should determine the enforcement of economic and social rights? Problems pertaining to the lack of legitimacy and competence often come up when the Court is involved in determining economic and social rights. These problems arise because a court is not democratically elected and is not equipped with necessary tools to deal with such a complex issue in economic and social rights. However, others believe that the Court’s involvement in determining economic and social rights can strengthen democracy since the Court may enforce matter that is not sufficiently addressed by the lawmaker. This paper will address the above issue in context of Indonesia. Should the Court involve in protecting economic and social rights? If so, how far the Court can go to determine economic and social rights? This paper acknowledges that economic and social rights are a broad and complex topic. Therefore, this paper limits the discussion by analyzing four selected judicial rulings which have significant impact in the protection of economic and social rights in Indonesia i.e. the judicial review cases on Electricity Law, Water Resources Law, National Education System Law and National Budget Law. This paper argues that it is necessary for the Court to involve in determining economic and social rights, especially when the lawmaker does not sufficiently address issues related to economic and social rights in its legislative product. The Court may fill the gaps in the protection of Economic and Social rights. The Court roles in this context, however, potentially encroach the authority of other branches of governments i.e. the executive and the legislative. Therefore, the Court roles should be carefully and strategically conducted so that it does not infringe the jurisdiction of the government and the lawmakers.